Wildcat memories : inside stories from Kentucky basketball greats - Brunk, Doug (The University Press of Kentucky, 2014)
Since the tenure of Coach Adolph Rupp, the University of Kentucky Wildcats men's basketball team has been a virtual powerhouse, repeatedly dominating the Southeastern Conference and garnering eight national titles. UK basketball is a homegrown tradition for sports enthusiasts, fostering a community that thrives on the camaraderie of fandom and devotedly cheers for its players in both victory and defeat. The individuals who have coached, played for, and inspired the Wildcats are important figures in Kentucky history and continue to motivate future athletes and passionate fans. Wildcat Memories i.